Mud volcanoes in the Gulf of Cadiz as a manifestation of tectonic processes and deep-seated fluid mobilization. (October 2021) - Xu, Shuhui; Menapace, Walter; Hüpers, Andre; Kopf, Achim
Abstract : Numerous mud volcanoes (MVs) are scattered through the Gulf of Cadiz (GoC), most of which are situated close to the WNW-ESE trending fault system in this region. In this study we have investigated six MVs in locations adjacent to major tectonic lineaments with the purpose of defining fluid and solid mobilization depth and ascent through the accretionary prism. Three of them, R2, D2 and Funky Monkey MVs, were discovered during RV Meteor cruise M149 in 2018. Their morphologies were characterized by multibeam bathymetry and vary from flat-topped to cone-shaped, reflecting different nature of the emitted products and variable degrees of activity. Mud breccias and pore fluids were sampled at the summits of all MVs to determine their physical properties and composition of the solid and liquid fractions. The physical properties and lithological changes demonstrate recent activity of Yuma, Ginsburg, Meknes and Funky Monkey MVs. At these sites, we traced back the origin of venting fluids to clay mineral dehydration through major and minor elements geochemistry, high content of illite in the mud breccia matrix and calculated reaction temperatures of 60–100 °C using the Mg–Li geothermometer. Differences in fluid composition imply a dominant clay dehydration signal in the shallow MVs and a stronger crustal input in the deeper MV (Funky Monkey). In contrast, R2 and D2 MVs are textbook inactive mud domes, showing no venting and a chemical composition/reaction temperature similar to seawater. If crustal input in MVs fluids will be confirmed by subsequent studies (e.g., through Sr isotopes), this could lead to a rethinking of fluid migration in the GoC, where transform faults (and MVs located close to them) focus the crustal signal from depth. Based on the MVs active state and the geochemistry of the fluids, we can distinguish which structure would be more suitable for further analyses (B isotopes, illite crystallinity) in order to identify possible sources of hydrocarbon-rich fluids channeled through MVs. Highlights: Six mud volcanoes of the Gulf of Cadiz are described through morphology, sedimentology, mineralogy and geochemistry. Three new mud volcanoes were discovered during expedition M149 on RV Meteor and hereby characterized for the first time. Morphology and geochemical signals show marked variations between different parts of the Gulf of Cadiz accretionary prism. Pronounced crustal input and reduced clay dehydration is present in deeper mud volcanoes located along strike-slip faults.